2021
DOI: 10.14260/jemds/2021/707
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Free Hand Dental Implant Placement in a Private Dental College Setup - A Radiographic Analysis

Abstract: BACKGROUND The factors that influence the implant accuracy are the anatomy of the patient, the experience of the practitioner and the surgical approach. However, the relative importance of each factor is poorly understood. Favourable function, occlusion, aesthetics and implant loading patterns can be obtained by optimal positioning. The experience of the surgeon is of utmost importance for the skill of placing a dental implant with proper angulation. The purpose of this retrospective study was to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…During free-hand surgery, practitioners need to consider the risk of approaching the root of an adjacent tooth. A study examining the relationship between the experience of the guide and implant angulation found that practitioners with less than 5 years of experience accounted for 9.3% of cases with 0-degree angulation, while those with 5-10 years and more than 10 years of experience accounted for 37.1% and 53.6%, respectively, of cases with 0-degree angulation [ 27 ]. From the above data analysis, it is apparently revealed that the accuracy of freehand placement is optimal especially in the posterior zones, considering that the opposing tooth angulation and occlusal patterns are taken into considerations thus the implant can be positioned in a 3D optimal position.…”
Section: Discussionmentioning
confidence: 99%
“…During free-hand surgery, practitioners need to consider the risk of approaching the root of an adjacent tooth. A study examining the relationship between the experience of the guide and implant angulation found that practitioners with less than 5 years of experience accounted for 9.3% of cases with 0-degree angulation, while those with 5-10 years and more than 10 years of experience accounted for 37.1% and 53.6%, respectively, of cases with 0-degree angulation [ 27 ]. From the above data analysis, it is apparently revealed that the accuracy of freehand placement is optimal especially in the posterior zones, considering that the opposing tooth angulation and occlusal patterns are taken into considerations thus the implant can be positioned in a 3D optimal position.…”
Section: Discussionmentioning
confidence: 99%